New method of apertured electromagnetic field modeling - Anokhov, S.; Khizhnyak, A.; Lymarenko, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Using a new wave treatment of rigorous Sommerfield’s solution for a problem of plane wave diffraction on a perfectly conductive half-plane, it was obtained the solution for a problem of plane wave diffraction on a slit and rectangular aperture. The result of aperture diffraction was represented as a sum of elementary rectangular unit cell waves. New integral approach to modeling of plane wave diffraction on an arbitrary two-dimensional aperture is discussed. Proposed method is very useful for providing numerical modeling of diffraction phenomena.